Teoria e ricerca sull'apprendimento del tedesco L2 Manuale per insegnanti in formazione - Ballestracci, Sabrina (Strumenti per la didattica e la ricerca, 2017)
Teoria e ricerca sull'apprendimento del tedesco L2 (Theory and research on learning German L2) is a technical-scientific manual designed for German language teaching courses in the context of training courses for future teachers. It offers an overview of the main theories and disciplines that deal with L2 language learning and teaching, describes the main research conducted on German L2 focusing on the particular case of guided learning for Italian speakers and, based on the results obtained from the research conducted so far, proposes a reflection focused on didactic. The volume is intended as a starting point for reflection also for teachers of German L2 already working in the schools as well as for researchers and scholars engaged in the study of language learning.